The effect of high intensity pulsed electric field on the coconut milk [electronic resource] - Mohd. Zaifulrizal Zainol, 1985- (2010)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2010